PERANCANGAN IKON CAGAR BUDAYA DAN MANUSKRIP DALAM LOGO OBJEK PEMAJUAN KEBUDAYAAN KOTA BANDUNG - Muhamad Rafli Ramdan; Martien Roos Nagara; Hadianto Hadianto (Jurusan Seni Rupa ISBI Bandung, 2024)
Icons are one of the main elements in communicating and introducing visual identity to the outside world. The design of cultural heritage icons and manuscripts in the Bandung City Cultural Advancement Object logo is one of the programs created by the Bandung City Government which is also written in Bandung City Regional Regulation No. 7 of 2023 concerning the Advancement of Culture. The Bandung City Disbudpar collaborated with lecturers and students at the Bandung College of Technology majoring in Visual Communication Design in the process of forming a visual identity in the form of the Bandung City OPK logo and icon. The design of cultural heritage icons and manuscripts was created to create a visual identity to preserve the rich history and cultural heritage of the city of Bandung. This icon is designed to include elements typical of cultural heritage and manuscripts. The Cultural Heritage icon represented by the classic architectural form of the roof of Bank Mandiri (EX–nedhandel N.V) on Jalan Asia Afrika No. 01, while manuscript icons can be found in manuscripts, fibers, books and chronicles. It is hoped that the design of the Bandung City OPK icon can become an icon that arouses a sense of pride, increases public awareness of cultural riches, and has an interest in cultural development that attracts the outside world and strengthens the image of the City of Bandung. Keywords: Icon Design, Cultural Heritage, Manuscripts, Logos, Bandung City ——————————————————————— Ikon menjadi salah satu elemen utama dalam mengkomunikasikan dan memperkenalkan identitas visual kepada dunia luar. Perancangan ikon cagar budaya dan manuskrip dalam logo Objek Pemajuan Kebudayaan Kota Bandung merupakan salah satu program yang dibuat oleh Pemerintah Kota Bandung yang juga tertulis di dalam Perda Kota Bandung No. 7 Tahun 2023 Tentang Pemajuan Kebudayaan. Disbudpar Kota Bandung melakukan berkolaborasi bersama dosen serta mahasiswa Sekolah Tinggi Teknologi Bandung jurusan Desain Komunikasi Visual dalam proses pembentukan identitas visual berupa logo dan ikon OPK Kota Bandung. Perancangan ikon cagar budaya serta manuskrip dibuat untuk menciptakan identitas visual untuk melestarikan kekayaan sejarah dan warisan budaya Kota Bandung. Ikon ini dirancang dengan memasukkan elemen khas cagar budaya dan manuskrip. Ikon Cagar Budaya yang diwakili oleh bentuk arsitektur klasik dari atap Bank Mandiri (EX–nedhandel N.V) di Jalan Asia Afrika No. 01, sementara ikon manuskrip dapat ditemui pada naskah, serat, kitab, dan babad. Perancangan ikon OPK Kota Bandung diharapkan dapat menjadi ikon yang membangkitkan rasa kebanggaan, meningkatkan kesadaran masyarakat terhadap kekayaan kebudayaan, serta memiliki minat terhadap pembangunan kebudayaan yang menjadi daya tarik dunia luar dan memperkuat citra Kota Bandung. Kata Kunci: Perancangan Ikon, Cagar Budaya, Manuskrip, Logo, Kota Bandung